The electronic properties of hydrogenated Janus MoSSe monolayer: a first principles investigation. (23rd August 2019) - Zhang, Xinxin; Song, Yi; Zhang, Fuchun; Fan, Qiang; Jin, Hong; Chen, Shanjun; Jin, Yuanyuan; Gao, Shufang; Xiao, Yi; Mwankemwa, Nsajigwa; Jiang, Long; Zhang, Weibin
Abstract: The geometry, stability and electronic properties of hydrogenated Janus MoSSe monolayer (MoSSe-H x ) ( x  = 0–16) were investigated by first-principles calculations. The most stable position for H adsorption on the surface of Janus MoSSe monolayer was studied. Energetically, Sets is the most favorable and stable site for H adsorption. Janus MoSSe-H x is predicted to be stable because its formation energy is lower than graphane and H2 S, and the adsorption energy is lower than H atoms adsorbed on graphene and MoS2 . The analysis of the electronic density distribution and bond population also show that Janus MoSSe-H x forms stable structure. Then, the variations of electronic structure of Janus MoSSe-H x were investigated. With the increase of the adsorbed numbers of H atoms, the density of state ( DOS ) of Janus MoSSe monolayer changed. It can be found that the DOS of Janus MoSSe-H2 has additional peaks in the band gap, which are introduced from H 1 s doping states. With the increase of H atoms adsorbed, there are more H 1 s doping states in the band gap. Correspondingly, the band gap of the Janus MoSSe-H x monolayer gradually decreases. The band gap of pristine Janus MoSSe is 1.47 eV, and the band gap of 2 H adsorbed on Janus MoSSe is 0.31 eV. When 16 H atoms are adsorbed on Se side of Janus MoSSe, the band gap is 0.23 eV. Also, the work function of the Janus MoSSe-H x monolayer was observed to decrease as the number of adsorbed H atoms increased. After hydrogenation process, the Se atoms transfer electrons to H atoms and Mo atoms, Mo atoms neutralize part of electrons, which leads to the weakening of the electric field pointing outward from Mo atoms to vacuum in the Janus MoSSe. As a result, the work function of the pristine Janus MoSSe is 5.24 eV, and the work function of Janus MoSSe-H x ( x  = 16) decreases to 3.70 eV. Therefore, our results provide a new method to realize band gap and work function modulation of Janus MoSSe by simple hydrogenation method. Our results suggest that the hydrogenated Janus MoSSe monolayer has potential applications in designing novel electronic and optical device, or photocatalyst such as water splitting with the intrinsic built-in electronic field.